The effects of EPHA2 inhibition on VEGF, VEGFR-1 and VEGFR-2 in human malignant glioma cells - Baharuddin, Wan Noor Ainun (2018)
Brain tumor “glioblastoma multiforme (GBM)” is assigned under fourth pathologic grades (grade IV) of astrocytic tumor. Despite various advances in the treatment modalities, median survival rate of GBM patients remains low between 12 to 14 months with a poor clinical prognosis. Human EphA2 gene plays an important role in regulating angiogenesis and known to be over expressed in GBM tumors. The elevated trend of EphA2 was associated to the poor prognosis of GBM patients, shorter survival rate and recurrence of the disease. This study aims to investigate the roles of EphA2 in angiogenesis signaling pathway governed by VEGF, VEGFR-1 and VEGFR-2. In this study, two types of cell lines derived from different origins were utilized. U-87MG cells were isolated from a patient with GBM type 4 diagnosis, whereas DBTRG-05MG was isolated from a GBM type 4 patient who underwent chemotherapy and radiotherapy. The effects of EphA2 gene silencing following transfection of small interfering RNA (siRNA) on the gene and protein expression of EphA2 and tumor angiogenesis related markers; VEGF, VEGFR-1 and VEGFR-2 were evaluated by using quantitative Real Time-PCR and Western blot analysis. This study showed downregulation of EphA2 mRNA (p=0.0061) had significantly downregulated VEGF (p=0.0123) and VEGFR-2 (p=0.0299) mRNA expression in U- 87MG cells. Consequently, at protein level there was no difference in VEGF expression (0.98-fold relative to 1-fold of non-transfected group), but decrement of VEGFR-2 expression by 0.51-fold was observed. As for DBTRG-05MG cells, downregulation of EphA2 mRNA (p=0.0137) had led to an increasing trend of VEGF mRNA expression (p=0.2131), but decreasing trend of VEGFR-2 (p=0.1453). Both differences were not statistically significant. At protein translational level, there was no difference of VEGF protein expression (0.92-fold relative to 1-fold of nontransfected group), but reducing VEGFR-2 protein by 0.61-fold decrease. This study also had shown that there was no VEGFR-1 gene and protein expression in both U- 87MG and DBTRG-05MG malignant glioma cells. Therefore, it was discovered that EphA2 plays an important role in VEGF/VEGFR-2 signaling in GBM cells. In conclusion, this study demonstrated that silencing EphA2 mRNA expression by siRNA led to the downregulation of gene and protein expression of VEGFR-2 without affecting VEGF secretion in malignant glioma cells. Interestingly, this study has successfully elucidated that EphA2 plays important roles in mediating angiogenesis through VEGFR-2 signaling.